HLA-DRB1 allele impact on pediatric multiple sclerosis in a Hellenic cohort. Issue 1 (February 2020) - Gontika, Maria; Skarlis, Charalampos; Artemiadis, Artemios; Pons, Roser; Mastroyianni, Sotiria; Vartzelis, George; Theodorou, Virginia; Kilindireas, Konstantinos; Stefanis, Leonidas; Dalakas, Marinos; Chrousos, George; Anagnostouli, Maria
Background: Pediatric-onset multiple sclerosis (POMS) is considered a complex disease entity with many genetic and environmental factors implicated in its pathogenesis. Linkage studies in Caucasian adult populations consistently demonstrate the major histocompatibility complex and its HLA (human leukocyte antigen) polymorphisms as the genetic locus most strongly linked to MS. Objective: To investigate the frequencies and possible clinical and imaging correlations of HLA-DRB1 alleles in a Hellenic POMS sample. Methods: Fifty POMS patients fulfilling the IPMSSG (International Pediatric Multiple Sclerosis Study Group) criteria were enrolled using 144 adult-onset MS (AOMS) patients and 246 healthy controls for comparisons. HLA genotyping was performed with standard low-resolution sequence-specific oligonucleotide (SSO) techniques. Clinical and imaging correlations with specific HLA-DRB1 alleles were also examined. Results: The HLA-DRB1*03 genotype was significantly higher in POMS patients compared to both the AOMS population (26% vs. 12.5%, p  = 0.042) and the general population (26% vs. 12.6%, p  = 0.004). HLA-DRB1*03 -positive POMS patients had significantly more relapses (6.9 ± 4.9 vs. 4.2 ± 4.4, p  = 0.005) and more thoracic spinal cord lesions than HLA-DRB1*03- negative patients (61.5% vs. 27%, p  = 0.043). Conclusion: In our Hellenic population, HLA-DRB1*03 allele confers increased risk for POMS and it is also correlated with possibly increased disease activity, expanding the existing knowledge on HLA associations and POMS.